On the sources of the great moderation - Galí, Jordi 1961-; Gambetti, Luca 1974- (NBER working paper series, 2008)
"The remarkable decline in macroeconomic volatility experienced by the U.S. economy since the mid-80s (the so-called Great Moderation) has been accompanied by large changes in the patterns of comovements among output, hours and labor productivity. Those changes are reflected in both conditional and unconditional second moments as well as in the impulse responses to identified shocks. Among other changes, our findings point to (i) an increase in the volatility of hours relative to output, (ii) a shrinking contribution of non-technology shocks to output volatility, and (iii) a change in the cyclical response of labor productivity to those shocks. That evidence suggests a more complex picture than that associated with "good luck" explanations of the Great Moderation"--National Bureau of Economic Research web site